Novel Protein Kinase Signaling Systems Regulating Lifespan Identified by Small Molecule Library Screening Using Drosophila - Spindler, Stephen R.; Li, Rui; Dhahbi, Joseph M.; Yamakawa, Amy; Sauer, Frank (PLOS ONE, 2012)
Protein kinase signaling cascades control most aspects of cellular function. The ATP binding domains of signaling protein kinases are the targets of most available inhibitors. These domains are highly conserved from mammals to flies. Herein we describe screening of a library of small molecule inhibitors of protein kinases for their ability to increase Drosophila lifespan. We developed an assay system which allowed screening using the small amounts of materials normally present in commercial chemical libraries. The studies identified 17 inhibitors, the majority of which targeted tyrosine kinases associated with the epidermal growth factor receptor (EGFR), platelet-derived growth factor (PDGF)/vascular endothelial growth factor (VEGF) receptors, G-protein coupled receptor (GPCR), Janus kinase (JAK)/signal transducer and activator of transcription (STAT), the insulin and insulin-like growth factor (IGFI) receptors. Comparison of the protein kinase signaling effects of the inhibitors in vitro defined a consensus intracellular signaling profile which included decreased signaling by p38MAPK (p38), c-Jun N-terminal kinase (JNK) and protein kinase C (PKC). If confirmed, many of these kinases will be novel additions to the signaling cascades known to regulate metazoan longevity.